Design and Implementation of Web Service Based Maintenance Interface for Train Door - ZHANG Wei; WANG Hai-li; ZHOU Xing-peng (机车电传动)
In this paper, current network topology of TCMS and its potential problems in maintenance between heterogeneous systems were briefly described, and an advanced maintenance interface based on industrial ethernet and web service technology to allow seamless integration between train devices, TCMS and remote train management system was expounded. As an example, the implementation of such a maintenance interface for electronic door control unit (EDCU) was also presented in this paper to demonstrate its real world application.